Transformasi Digital UMKM Hilal Berkah melalui Pemanfaatan Media Sosial dalam Mendukung Pemberdayaan Ekonomi Masyarakat di Desa Ulukonaweha Kabupaten Kolaka - Sarinah . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Digital transformation has become one of the essential strategies in supporting the development of Micro, Small, and Medium Enterprises (MSMEs) in the digital economy era. The utilization of social media provides opportunities for MSMEs to expand market access, enhance product promotion, and strengthen business competitiveness. This study aims to analyze the implementation of digital transformation through the use of social media in Hilal Berkah MSMEs located in Ulukonaweha Village, Samaturu District, Kolaka Regency, in supporting community economic empowerment. This research employed a descriptive qualitative approach with data collection techniques conducted through observation, interviews, and documentation. The results indicate that the utilization of social media platforms such as WhatsApp, Facebook, and Instagram has been able to increase product visibility, expand marketing networks, and improve community business income. However, the digital transformation process still faces several challenges, including low digital literacy, limited human resources, and inadequate product branding capabilities. Therefore, government support, academic assistance, and strengthening community digital capacity are needed to create a sustainable digital-based MSME ecosystem. This study confirms that the digital transformation of MSMEs not only impacts economic aspects but also contributes to the social and institutional empowerment of rural communities.